A Comparative Electrochemical Behaviour Study and Analytical Detection of the p-Nitrophenol Using Silver Solid Amalgam, Mercury, and Silver Electrodes. (26th May 2011) - De Souza, Djenaine; Mascaro, Lucia H.; Fatibello-Filho, Orlando
Abstract : This work reports a comparative electrochemical behaviour study and p-nitrophenol analytical detection using silver solid amalgam, hanging dropping mercury, and silver electrodes. For this, square wave voltammetry was employed, where the analytical responses and the redox mechanisms could be compared for reduction processes of 4-nitrophenol by analysis of the voltammetric responses. The analytical performance of the electrode was evaluated and detection and quantification limits, recovery percentages, repeatability, and reproducibility for the silver solid amalgam and hanging dropping mercury electrodes presented similar values; the results presented for the silver electrode indicated worse analytical parameters than the other electrodes. The results indicate that the silver solid amalgam electrode can be considered a suitable tool and an interesting alternative for the analytical determination of 4-nitrophenol, as well as for the determination of other biological and environmentally interesting compounds that present analytical responses on mercury surfaces.